DINAMIKA PENGEMBANGAN PESANTREN BERWAWASAN LINGKUNGAN (EKO-PESANTREN) DI PONDOK PESANTREN SURYALAYA - Akbar, Akhmad Hidayat Nurul; Setiawan, Iwan; Noor, Trisna Insan (Universitas Galuh, 2023)
Islamic boarding schools are the oldest Islamic educational institutions in Indonesia which were founded by scholars. Islamic boarding schools were established in order to educate people to understand and implement Islamic teachings by emphasizing the importance of religious morality as a way of life. In social and national life, Islamic boarding schools can play a major role in efforts to save the environment, among others by providing insight and awareness about the importance of protecting the environment as part of the practice of religious teachings. This research was conducted at the Suryalaya Islamic Boarding School which is one of the Islamic Boarding Schools in Tasikmalaya, West Java, which has received the Kalpataru Award, namely the Highest Awardfrom the Government of the Republic of Indonesia in the environmental sector with category C in the field of Greening activities. The purpose of this research is to provide an overview of the dynamics of implementation boarding schools with environmental insight (Eko Pesantren) from the period 1905-1952 (preparatory period) and the period 1952-2011 (implementation period) and the period from 2011 to the present (sustainability). The method used in this study is a qualitative method with grounded theory research as a data analysis technique. The results of the study show that the Suryalaya Islamic Boarding School has implemented eco-Islamic boarding schools in its activities which are divided into preparation, implementation and sustainability stages. The activities carried out by the Suryalaya Islamic Boarding School are related to environmentally sound activities, especially economic, social and ecological activities that have an impact on the lives of the surrounding community. Related to this, the Suryalaya Islamic Boarding School has implemented several strategies in the economic, social and environmental fields in the framework of implementing Eco-Islamic Boarding Schools within the Suryalaya Islamic Boarding School environment.